Handbook of Research on Estimation and Control Techniques in E-Learning Systems - Mkrttchian; Bershadsky; Bozhday; Kataev specialist in the field of informatics and computer engineering Professor of Yurga technological Institute of Tomsk Polytechnic University, doctor of technical sciences; Kataev (IGI Global, 2015)
Improvements in the application of online learning technologies are continually on the rise as the expectation for individuals to obtain a higher education grows and more people are seeking alternative modes of education. As more institutions implement e-learning systems, it has become increasingly important to explore the advancements and obstacles of these technologies.The Handbook of Research on Estimation and Control Techniques in E-Learning Systems presents the latest research in online learning and educational technologies for a diverse range of students and educational environments. Featuring comprehensive coverage on the implementation and usage of e-education systems, this publication explores a variety of pertinent topics including, but not limited to, ubiquitous computer technology, e-learning environments, and challenges in implementing these technologies, serving as a crucial reference source for researchers, professionals, academicians, students, government officials, and technology developers interested in the adoption and implementation of e-learning systems.